Thailand Economic Monitor, November 2005 - World Bank (World Bank, Bangkok, 2021)
This paper tracks Thailand's economic performance for 2005-2006, particularly its economic growth rate, poverty headcount, oil pricing impacts, investment environment, competitiveness strategy, and infrastructure efficiency, as well as its trade, financial and corporate sector reforms. After an overview in Section 1, Section 2 examines Thailand's economic recovery and outlook, and section 3 focuses on the implementation of structural reforms. Appendix 1 details the country's key economic indicators and appendix 2 comprises matrices for structural reform implementation, including poverty reduction diagnostics and social protection.